SOLIDARITY POPULAR ECONOMY AND SOLIDARITY TECHNO-SCIENCE IN LATIN AMERICA: A SYSTEMATIC REVIEW (Interdisciplinary Studies Journal, 2025)
This literature review set out to examine the body of research addressing the relationship between the Popular Solidarity Economy (PSE) and Solidarity Technoscience (ST) in Latin America, with a focus on identifying prevailing themes, methodological approaches, and key findings. To this end, searches were conducted in the Scopus, Web of Science (WOS), and Science Direct databases, using terms associated with transformative economies, and including studies published between 2010 and 2023. The resulting corpus was analyzed through the Iramuteq lexical analysis software. The findings suggest that Solidarity Technoscience, as an emerging concept, is primarily situated within discussions on technology transfer and Solidarity Economy in the broader field of alternative economies. Lexical analyses revealed significant recurrences and co-occurrences of terms such as social, science, community, public, economy, technology, change, politics, and development, thereby underscoring both the relevance and the conceptual breadth of the topic in the scientific literature under review.
Keywords: Solidarity Popular Economy; Sociotechnical Appropriateness; Latin America